A global introduction to Baptist churches - Johnson, Robert E. (Introduction to religion, 2010)
Coinciding with the four-hundredth anniversary of the birth of the Baptist movement, this book explores and assesses the cultural sources of Baptist beliefs and practices. Although the movement has been embraced, enriched, and revised by numerous cultural heritages, the Baptist movement has focused on a small group of Anglo exiles in Amsterdam in constructing its history and identity. Robert E. Johnson seeks to recapture the varied cultural and theological sources of Baptist tradition and to give voice to the diverse global elements of the movement that have previously been excluded or marginalized. With an international communion of over 110 million persons in more than 225,000 congregations, Baptists constitute the world's largest aggregate of evangelical Protestants. This work offers insight into the diversity, breadth, and complexity of the cultural influences that continue to shape Baptist identity today